Antimony-based new energy battery negative electrode material and preparation method thereof

CN122992050APending Publication Date: 2026-10-27GUIZHOU HUAXING METALLURGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611040556.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

此类物理混合方式难以实现分子级别的均匀性,限制了材料电化学性能的进一步提升

Benefits of technology

刚性苯环核心:提供一个刚性的、几何结构明确的中心骨架,有利于构筑Sb-MOFs结构。苯环在后续煅烧过程中,可作为原位碳源,转化为导电碳骨架。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992050A_ABST
    Figure CN122992050A_ABST
Patent Text Reader

Abstract

The application relates to the field of lithium ion batteries, in particular to a Sb-based new energy battery negative electrode material and a preparation method thereof, which is obtained by reacting Sb-MOFs precursors with a phosphorus source, wherein the Sb-MOFs precursors are obtained by reacting an antimony source and an aromatic organic acid ligand; the negative electrode material provided by the application presents a unique porous spherical morphology, rich pores and a stable spherical profile, which not only provides a rapid transmission channel for lithium ions, but also endows the material with excellent electrolyte wettability and structural self-supporting capacity, so that the material exhibits high specific capacity and excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, specifically to an antimony-based anode material for new energy batteries and its preparation method. Background Technology

[0002] With the rapid development of portable electronic devices, electric vehicles, and large-scale energy storage grids, the demand for rechargeable batteries with high energy density, long cycle life, and fast charge / discharge capabilities is becoming increasingly urgent. Currently, commercially available lithium-ion battery anode materials mainly use graphite-based carbon materials, with a theoretical specific capacity of only 372 mAh / g, which is insufficient to meet the requirements of next-generation high-performance batteries. Therefore, the development of novel high-capacity anode materials has become a research hotspot.

[0003] Among numerous candidate materials, antimony-based materials have attracted widespread attention due to their high theoretical lithium storage capacity and suitable operating potential platform. Antimony phosphate, as a novel anode material, exhibits a high theoretical capacity due to multi-electron reactions in lithium / sodium storage. However, antimony phosphate alone suffers from poor electronic conductivity, slow ion transport, and structural degradation caused by volume changes during cycling. Therefore, combining antimony phosphate with carbon materials is an inevitable choice. In existing technologies, the preparation of antimony phosphate / carbon composites mostly employs external mixing methods, i.e., antimony phosphate and carbon sources are combined through ball milling or similar processes. Such physical mixing methods struggle to achieve molecular-level homogeneity, limiting further improvements in the material's electrochemical performance. Summary of the Invention

[0004] Purpose of the invention: To address the above-mentioned technical problems, this invention proposes an antimony-based anode material for new energy batteries and its preparation method.

[0005] The technical solution adopted is as follows: An antimony-based anode material for new energy batteries is obtained by reacting an Sb-MOFs precursor with a phosphorus source.

[0006] As a further improvement of the present invention, the Sb-MOFs precursor is obtained by reacting an antimony source with an aromatic organic acid ligand.

[0007] As a preferred embodiment of the above scheme, the antimony source is antimony acetate. Antimony acetate has good solubility in organic solvents, and its acetate ion, as a weak coordinating group, is easily replaced by polydentate ligands in solvothermal reactions, which is beneficial for coordination self-assembly reactions with aromatic organic acid ligands to construct structurally regular Sb-MOF precursors. Simultaneously, the acetate itself escapes during calcination, without introducing non-volatile impurity ions, ensuring the quality of the final product.

[0008] As one of the core innovations of this invention, the structural formula of the aromatic organic acid ligand is as follows:

[0009] R1, R2, R3, R4, R5, and R6 are each independently hydrogen, carboxyl, or phosphate groups, and R1, R2, R3, R4, R5, and R6 are not all hydrogen at the same time, and at least one is a phosphate group.

[0010] This ligand structure design concept is key to the success of the technical solution of this invention. Its theoretical basis and advantages are as follows: Rigid benzene ring core: Provides a rigid, geometrically well-defined central framework, which is beneficial for constructing Sb-MOFs structures. During subsequent calcination, the benzene ring can serve as an in-situ carbon source, transforming into a conductive carbon framework.

[0011] Multiple coordination functional groups: Carboxyl and phosphate groups are introduced as coordinating groups onto the benzene ring. These oxygen-containing functional groups interact with Sb. 3+ They all have strong coordination capabilities, which can ensure the formation of a stable MOF framework.

[0012] In-situ introduction of phosphorus: Aromatic polydentate ligands containing phosphate groups were selected for the synthesis of Sb-MOF precursors. Both the phosphate and carboxyl groups can react with Sb. 3+ Strong coordination occurs, causing phosphorus to be uniformly and precisely anchored at the periodic lattice nodes of the MOF framework in the form of Sb-OP chemical bonds at the molecular scale. These isolated and anchored Sb-OP structural units, separated by organic ligands, constitute atomically dispersed "antimony phosphate precursor seeds." Due to the steric hindrance and charge balance requirements of the coordinating groups within the MOF framework, the phosphate groups inherent in the ligands alone are often insufficient to achieve the stoichiometry required for the final target product. Therefore, by adding an appropriate amount of phosphorus source, sufficient reactants can be provided for the full generation of the antimony phosphate active phase. In the subsequent heat treatment stage, as the temperature rises, the organic components of the Sb-MOF framework gradually decompose into a conductive carbon skeleton, and the exogenous phosphorus source decomposes simultaneously to generate active phosphorus species. At this point, the pre-constructed atomic-level Sb-OP nucleation centers have high thermodynamic stability and preferentially become the formation sites for antimony phosphate crystal nuclei, significantly reducing the nucleation barrier. The active species generated by the decomposition of exogenous phosphorus can participate in the reaction within a very short diffusion distance, enabling the antimony phosphate crystal nuclei to grow in situ, uniformly, and controllably on the carbon skeleton.

[0013] More preferably, two of R1, R2, R3, R4, R5, and R6 are hydrogen groups, and the rest are carboxyl and phosphate groups.

[0014] More preferably, three of R1, R2, R3, R4, R5, and R6 are hydrogen groups, and the rest are carboxyl and phosphate groups.

[0015] More preferably, four of R1, R2, R3, R4, R5, and R6 are hydrogen groups, and the rest are carboxyl and phosphate groups.

[0016] More preferably, the aromatic organic acid ligand may be selected from the following compounds: .

[0017] It should be noted that the above examples are merely preferred examples. Any polydentate ligand that simultaneously contains at least one phosphate group on the benzene ring skeleton should be understood as falling within the protection scope of this invention.

[0018] The present invention also provides a method for preparing the antimony-based new energy battery anode material according to any one of the above claims: The Sb-MOFs precursor is mixed with a certain amount of phosphorus source, and then the resulting mixture is calcined under a specific atmosphere and temperature to obtain the antimony-based new energy battery anode material.

[0019] Preferably, the Sb-MOFs precursor and phosphorus source are mixed using mechanical ball milling or grinding. This premixing of the Sb-MOFs precursor and phosphorus source increases the reaction contact area and, through mechanochemical effects, refines the powder particles, generates lattice defects and local high temperature and pressure, lowers the activation energy of subsequent solid-phase reactions, improves reaction activity, and promotes the completion of the conversion reaction at a lower temperature.

[0020] Preferably, the phosphorus source is ammonium dihydrogen phosphate and / or sodium dihydrogen phosphate. These two dihydrogen phosphate salts are chosen as external supplementary phosphorus sources based on the following considerations: they decompose at high temperatures, releasing highly reactive phosphorus species that can efficiently react with the antimony component in the Sb-MOF precursor to generate antimony phosphate; and the byproducts escape in gaseous form, thus avoiding the introduction of difficult-to-remove impurities into the final anode material.

[0021] Preferably, the mass ratio of the Sb-MOF precursor to the phosphorus source is 1:9 to 9:1. By adjusting this ratio, the stoichiometric ratio of antimony and phosphorus in the final product can be systematically controlled. The inventors found that when the mass ratio is approximately 1:1, the prepared anode material exhibits excellent electrochemical performance.

[0022] Preferably, the calcination temperature is 600-800℃. Below 600℃, the driving force for the solid-phase reaction is insufficient, resulting in incomplete formation of the antimony phosphate crystal phase and poor product crystallinity. Above 800℃, the generated antimony phosphate grains may undergo severe growth and agglomeration, destroying the nanostructure inherited from the Sb-MOF precursor.

[0023] Preferably, the calcination treatment is carried out under an inert atmosphere, namely nitrogen or argon. Using an inert atmosphere ensures that the organic ligand components in the Sb-MOF precursor are pyrolyzed into a conductive carbon framework, rather than being oxidized and ablated.

[0024] As a further improvement of the present invention, the negative electrode material prepared by the present invention has a porous spherical structure.

[0025] The morphology formation mechanism may be as follows: In the solvothermal synthesis stage, the reaction system, driven by the tendency to reduce surface energy, causes the initially formed Sb-MOF microcrystals to aggregate into aggregates with high sphericity for stable existence. Subsequently, in the grinding or ball milling process, these irregular initial aggregates, together with the phosphorus source, are forcibly compacted, encapsulated, and shaped under repeated impact, shearing, and kneading, ultimately forming dense spherical agglomerates with uniform composition and controllable size, which constitute the direct physical template for the final spherical structure. In the calcination stage, the Sb-MOF precursor inside the spherical agglomerates undergoes pyrolysis, and the phosphorus source tightly encapsulated or embedded within them also decomposes. Gas escapes from the confined geometric space inside the spherical particles to the outside, creating pores in situ inside the particles, thereby creating a well-developed internal pore network while maintaining the macroscopic spherical outline.

[0026] It should be noted that the above-mentioned mechanism of action is a theoretical explanation based on the experimental phenomena of this invention. The accuracy of this theoretical explanation does not affect the inventiveness of the technical solution of this invention or the scope of patent protection.

[0027] The technical solution provided by this invention has the following significant beneficial effects: The antimony-based new energy battery anode material and its preparation method provided by this invention utilize an aromatic ligand containing phosphate groups to construct an Sb-MOF precursor, precisely pre-anchoring phosphorus and carbon elements around antimony atoms at the molecular scale. Combined with a subsequently added phosphorus source, a composite structure is generated in situ through mechanical ball milling and temperature-controlled calcination, in which antimony phosphate nanocrystals are uniformly embedded in a porous carbon framework. This significantly improves the interfacial bonding strength between the active phase and the carbon matrix, fundamentally alleviating the severe volume expansion and pulverization during charging and discharging. The obtained anode material exhibits a unique porous spherical morphology. The abundant pores and stable spherical profile not only provide a rapid transport channel for lithium ions but also endow the material with excellent electrolyte wettability and structural self-supporting ability, enabling it to exhibit high specific capacity and excellent cycle stability. Attached Figure Description

[0028] Figure 1 This is a cross-sectional SEM image of the negative electrode material prepared in Example 1. Detailed Implementation

[0029] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Techniques not mentioned in this invention refer to existing technologies. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0030] Example 1: A method for preparing an antimony-based anode material for new energy batteries: 2.98 g of antimony acetate was added to 40 mL of methanol and stirred until completely dissolved to obtain solution A. 3.18 g of benzene-1,3,5-triphosphoric acid (CAS: 4672-29-1) was added to another 40 mL of methanol and stirred until completely dissolved to obtain solution B. Solutions A and B were mixed and stirred for 30 minutes. The mixture was then transferred to a polytetrafluoroethylene-lined high-pressure reactor, sealed, and reacted at 100℃ for 24 hours. After natural cooling to room temperature, the precipitate was collected by filtration, washed three times with methanol and deionized water, and finally dried under vacuum at 80℃ for 12 hours to obtain SbMOF precursor powder. 0.5 g of the above SbMOF precursor powder and 0.5 g of ammonium dihydrogen phosphate were placed in a mortar and ground until thoroughly mixed. The resulting uniformly mixed powder was transferred to a tube furnace and calcined at 700℃ at a rate of 5℃ / min under an argon atmosphere for 3 hours. After natural cooling, the negative electrode material was obtained. Its cross-sectional SEM image is shown below. Figure 1 .

[0031] Example 2: This example is basically the same as Example 1, except that the same amount of 1,3-phthalic acid-5-phosphoric acid (CAS: 25062-54-8) is used instead of benzene-1,3,5-triphosphoric acid (CAS: 4672-29-1).

[0032] A method for preparing an antimony-based anode material for new energy batteries: 2.98 g of antimony acetate was added to 40 mL of methanol and stirred until completely dissolved to obtain solution A. 2.46 g of 1,3-phthalic acid-5-phosphoric acid was added to another 40 mL of methanol and stirred until completely dissolved to obtain solution B. Solutions A and B were mixed and stirred for 30 minutes. The mixture was then transferred to a polytetrafluoroethylene-lined high-pressure reactor, sealed, and reacted at 100°C for 24 hours. After natural cooling to room temperature, the precipitate was collected by filtration, washed three times with methanol and deionized water, and finally dried under vacuum at 80°C for 12 hours to obtain SbMOF precursor powder. 0.5 g of the above SbMOF precursor powder and 0.5 g of ammonium dihydrogen phosphate were placed in a mortar and ground until thoroughly mixed. The resulting uniformly mixed powder was transferred to a tube furnace and calcined at 700°C at a rate of 5°C / min under an argon atmosphere for 3 hours. After natural cooling, the negative electrode material was obtained.

[0033] Example 3: This example is basically the same as Example 1, except that the same amount of 3,5-diphosphonobenzoic acid (CAS: 1192028-87-7) is used instead of benzene-1,3,5-triphosphate (CAS: 4672-29-1).

[0034] A method for preparing an antimony-based anode material for new energy batteries: 2.98 g of antimony acetate was added to 40 mL of methanol and stirred until completely dissolved to obtain solution A. 2.82 g of 3,5-diphosphonobenzoic acid was added to another 40 mL of methanol and stirred until completely dissolved to obtain solution B. Solutions A and B were mixed and stirred for 30 minutes. The mixture was then transferred to a polytetrafluoroethylene-lined high-pressure reactor, sealed, and reacted at 100°C for 24 hours. After natural cooling to room temperature, the precipitate was collected by filtration, washed three times with methanol and deionized water, and finally dried under vacuum at 80°C for 12 hours to obtain SbMOF precursor powder. 0.5 g of the above SbMOF precursor powder and 0.5 g of ammonium dihydrogen phosphate were placed in a mortar and ground until thoroughly mixed. The resulting uniformly mixed powder was transferred to a tube furnace and calcined at 700°C at a rate of 5°C / min under an argon atmosphere for 3 hours. After natural cooling, the negative electrode material was obtained.

[0035] Example 4: This example is basically the same as Example 1, except that the calcination temperature is 600℃.

[0036] Example 5: This example is basically the same as Example 1, except that the calcination temperature is 800℃.

[0037] Comparative Example 1: This comparative example is essentially the same as Example 1, except that the same amount of mesitylene benzoic acid (CAS: 554-95-0) is used instead of benzene-1,3,5-triphosphate (CAS: 4672-29-1). Details are as follows: A method for preparing an antimony-based anode material for new energy batteries: 2.98 g of antimony acetate was added to 40 mL of methanol and stirred until completely dissolved to obtain solution A. 2.46 g of tribenzoic acid was added to another 40 mL of methanol and stirred until completely dissolved to obtain solution B. Solutions A and B were mixed and stirred for 30 minutes. The mixture was then transferred to a high-pressure reactor lined with polytetrafluoroethylene (PTFE), sealed, and reacted at 100 °C for 24 hours. After natural cooling to room temperature, the precipitate was collected by filtration, washed three times with methanol and deionized water, and finally dried under vacuum at 80 °C for 12 hours to obtain SbMOF precursor powder. 0.5 g of the above SbMOF precursor powder and 0.5 g of ammonium dihydrogen phosphate were placed in a mortar and ground until thoroughly mixed. The resulting uniformly mixed powder was transferred to a tube furnace and calcined at 700 °C at a rate of 5 °C / min under an argon atmosphere for 3 hours. After natural cooling, the negative electrode material was obtained.

[0038] Comparative Example 2: This comparative example is basically the same as Example 1, except that ammonium dihydrogen phosphate is not added. Details are as follows: A method for preparing an antimony-based anode material for new energy batteries: 2.98 g of antimony acetate was added to 40 mL of methanol and stirred until completely dissolved to obtain solution A. 3.18 g of benzene-1,3,5-triphosphoric acid (CAS: 4672-29-1) was added to another 40 mL of methanol and stirred until completely dissolved to obtain solution B. Solutions A and B were mixed and stirred for 30 minutes. The mixture was then transferred to a polytetrafluoroethylene-lined high-pressure reactor, sealed, and reacted at 100℃ for 24 hours. After natural cooling to room temperature, the precipitate was collected by filtration, washed three times with methanol and deionized water, and finally dried under vacuum at 80℃ for 12 hours to obtain SbMOF precursor powder. 0.5 g of the above SbMOF precursor powder was placed in a mortar and ground thoroughly. The resulting powder was transferred to a tube furnace and calcined at 700℃ under an argon atmosphere at a rate of 5℃ / min for 3 hours. After natural cooling, the negative electrode material was obtained.

[0039] Comparative Example 3: This comparative example is essentially the same as Example 1, except that commercially available antimony trioxide (average particle size 1 μm) is used instead of SbMOF. Details are as follows: Take 0.5 g of commercially available antimony trioxide (average particle size 1 μm) and 0.5 g of ammonium dihydrogen phosphate and grind them in a mortar to mix them thoroughly. Transfer the resulting uniformly mixed powder to a tube furnace and heat it to 700 °C at 5 °C / min under an argon atmosphere. Hold it at the temperature for 3 hours and then cool it naturally to obtain the negative electrode material.

[0040] Performance testing: The negative electrode materials prepared in Examples 1-5 and Comparative Examples 1-3 of this invention were used as samples for performance testing. The sample, acetylene black, and polyvinylidene fluoride were weighed at a mass ratio of 7:2:1, ground evenly in a mortar, and a slurry was prepared using an appropriate amount of N-methyl-2-pyrrolidone as a solvent. The slurry was coated onto copper foil and then dried in a vacuum oven at 130°C for 12 hours. After cooling to room temperature, it was removed and cut into pieces with an area of ​​approximately 1 cm² using a punch. 2 The electrode plates are placed in a vacuum drying oven for later use.

[0041] The coin cell (model 2032) was assembled in a glove box filled with high-purity argon gas, where the water and oxygen content were both less than 0.1 ppm. A lithium metal sheet was used as the counter electrode, and a Celgard 2400 microporous polypropylene membrane was used to separate the lithium sheet and the electrode. The electrolyte was 1 mol / L LiPF6 / EC+DEC (volume ratio 1:1). After standing for 20 hours, constant current charge-discharge tests were performed in the range of 0.01-3.00 V. First, the electrode material was activated by 10 cycles at 0.1 A / g, followed by 500 cycles at 1 A / g.

[0042] The test results are shown in Table 1 below.

[0043] Table 1:

[0044] As shown in Table 1 above, the negative electrode material prepared by this invention has excellent electrochemical performance.

[0045] The comparison of Examples 1-3 shows that the functional group type of aromatic organic acid ligands has a significant impact on the final electrochemical performance of the anode material.

[0046] A comparison of Examples 1 and 4-5 shows that calcination temperature is a key factor in controlling the performance of electrode materials. Too low a temperature leads to incomplete solid-phase reactions. Too high a temperature can easily cause excessive growth or even sintering of the active material grains, posing a potential risk to the microstructural stability during long-term cycling.

[0047] The comparison between Example 1 and Comparative Example 1 shows that the introduction of phosphate groups in the aromatic organic acid ligand structure has a positive effect on improving the final electrochemical performance of the anode material.

[0048] The comparison between Example 1 and Comparative Example 2 shows that the addition of exogenous phosphorus has a certain synergistic effect on improving the final electrochemical performance of the anode material.

[0049] The comparison between Example 1 and Comparative Example 3 shows that the Sb-MOF precursor method has an overwhelming advantage over the traditional solid-phase method.

[0050] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An antimony-based anode material for new energy batteries, characterized in that, It is obtained by reacting Sb-MOFs precursors with a phosphorus source.

2. The antimony-based new energy battery anode material as described in claim 1, characterized in that, The Sb-MOF precursor was obtained by reacting an antimony source with an aromatic organic acid ligand.

3. The antimony-based new energy battery anode material as described in claim 2, characterized in that, The structural formula of the aromatic organic acid ligand is as follows: R1, R2, R3, R4, R5, and R6 are each independently hydrogen, carboxyl, or phosphate groups, and R1, R2, R3, R4, R5, and R6 are not all hydrogen at the same time, and at least one is a phosphate group.

4. The antimony-based new energy battery anode material as described in claim 3, characterized in that, Two of R1, R2, R3, R4, R5, and R6 are hydrogen groups, and the rest are carboxyl and phosphate groups.

5. The antimony-based new energy battery anode material as described in claim 3, characterized in that, Three of R1, R2, R3, R4, R5, and R6 are hydrogen groups, while the rest are carboxyl and phosphate groups.

6. The antimony-based new energy battery anode material as described in claim 3, characterized in that, Four of R1, R2, R3, R4, R5, and R6 are hydrogen groups, while the rest are carboxyl and phosphate groups.

7. A method for preparing an antimony-based new energy battery anode material as described in any one of claims 1-6, characterized in that, The Sb-MOFs precursor and phosphorus source are mixed, ball-milled, and then calcined under an inert atmosphere.

8. The method for preparing the antimony-based new energy battery anode material as described in claim 7, characterized in that, The phosphorus source is sodium dihydrogen phosphate and / or ammonium dihydrogen phosphate.

9. The method for preparing the antimony-based new energy battery anode material as described in claim 7, characterized in that, The mass ratio of Sb-MOF precursor to phosphorus source is 1-9:1-9.

10. The method for preparing the antimony-based new energy battery anode material as described in claim 7, characterized in that, The calcination temperature is 600-800℃.